Floating phalanx; simultaneous double dislocation of the interphalangeal joint in a finger: A case report and literature review - ŞİRİN, EVRİM (My University, 2022)
Isolated proximal and distal interphalangeal joint (DIPJ) dislocations are widely seen as a result of sporting injuries and major trauma. The combination of dorsal dislocation of the DIPJ in the same finger concomitant to traumatic dorsal dislocation of the proximal interphalangeal joint (PIPJ) is a rarely seen injury. The case is, here, presented of a 65-year-old female patient with proximal and DIPJ dislocation of the right-hand ring finger accompanied by volar and dorsal plate injuries in the proximal and distal joints.With this case, it was aimed to introduce a new term of \"floating phalanx\" into medical literature.The treatment was applied to the patient of closed reduction under peripheral block and the application of an aluminium finger splint in semiflexion. In a 24-month follow-up period, the 4th finger of the patient was observed to be stable and has pain-free range of movement. This case is an uncommon case of volar and dorsal plate avulsion fractures with PIPJ and DIPJ dorsal dislocation treated successfully with closed reduction and conservative treatment with excellent functional results.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Acil Tıp; Medicine; Health Sciences; Surgery Medicine Sciences; Emergency Medicine; ACİL TIP; Klinik Tıp; Klinik Tıp (MED); EMERGENCY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Acil Tıp Hizmetleri; Emergency Medical Services; Interphalangeal joints dislocation; phalanx dislocation; volar plate injury